Pengaruh Model Penemuan Terbimbing Terhadap Hasil Belajar Siswa SMP PAB 2 Helvetia - Rambe, Siti Fatimah; Nasution, Marah Doly; Irvan, Irvan (Universitas Batanghari Jambi, 2022)
The purpose of this study is to know the effectiveness of guided discovery learning model on students' cognitive abilities. The method used is a quasi-experimental study by adapting a Posttest-Only-Control Group design. Regarding the population, the researcher assigned class VIII of SMP PAB 2 Helvetia Medan, class VIII-1 and class VIII-2 research subjects as experimental and control classes, respectively, each class consisted of 30 students taken using a non-random technique. A test instrument in the form of a posttest consisting of 10 questions was used during data collection. The results showed that the average value of student learning outcomes that were treated in the form of guided exploratory learning models compared to the control class that used conventional learning models had a better value. Thus, it can be concluded that the application of the guided exploration method affects the student's learning outcomes in geometry teaching materials